Efektivitas Layanan Informasi Terhadap Pemilihan Karir Dalam Melanjutkan Pendidikan Ke Jenjang (SMA/SMK) - Shinta, Ratih Kumala; Adiningtyas, Sri Wahyuni; Hasibuan, Wilda Fasim (Jurnal Bimbingan dan Konseling Pandohop, 2023)
Based on the initial survey, the provision of information services to students as a reference for students who have an understanding of careers that seems still low, is thought to be due to the low desire and willingness of students towards high school and low information about talent and interest in the selection of secondary schools. The purpose of this study is to reveal the effectiveness of information services on career choice in continuing education at the SMA/SMK level. This research was carried out using quantitative methods with the type of pre-experimental research with The One Group Pretest-Posttest. The selection of research subjects used cluster sampling and those who were selected as samples were class IX 1 as the experimental group. The experimental group consisted of 48 students. The instrument used is a questionnaire. Data analysis used One Sample T-Test with SPSS 20 program. The research findings indicate that the factors that influence the effectiveness of information services on career selection are motivation, intelligence, talents and interests of students. This can be seen from the experimental group in the pretest and posttest with a significance of 0.000 or a probability below alpha (0.000 <0.05) with an increase in the score of the research subjects from an average score of 32.9% to 35.78%. Based on the findings above, it can be concluded that this information service is effective in continuing career selection at the SMA/SMK level. This study shows the importance of implementing information services in schools by BK teachers.